Determining the Factors Affecting on Digital Learning Adoption among the Students in Kathmandu Valley: An Application of Technology Acceptance Model (TAM) - Shankar Bhattarai; Sanjeev Maharjan (International Journal of Engineering and Management Research, 2020)
This study investigated students’ perception towards acceptance of digital transformation in teaching-learning activities studying at different levels in Kathmandu valley (includes 3 districts: Kathmandu, Lalitpur, and Bhaktapur), Nepal. Using the Technology Acceptance Model (TAM) as a research framework to examine the factors affecting how students come to accept and use technology. The literature review indicated that social influence, accessibility, computer self-efficacy, infrastructure, and perceived enjoyment were the most common external factors of TAM. A total of 384 students were participated in the study. Different statistical analyses have been performed in order to test the significance of the considered factors that may affect the digital learning practices of students. The result of the data analysis revealed that social influence, accessibility, computer self-efficacy, infrastructure, and enjoyment have a significant impact on perceived ease of use of the digital learning system. Furthermore, social influence, accessibility, computer self-efficacy, infrastructure, and enjoyment were also found to have a positive influence on the perceived usefulness of the digital learning system. The Digital learning system is changing the traditional practice of learning with technology and innovation. The study support that using digital tools in education makes academic activities more interesting, easy to access, creative, effective, and productive.